A Model Development Of Organosolv Pretreatment For Various Types Of Biomass - Lim, Siew Che (2020)
Organosolv pretreatment is declared as a reliable approach to transform lignocellulosic biomass into sustainable energy, such as biofuel and value-added chemicals. A comprehensive study of organosolv pretreatment for coconut husk, spent coffee ground and sugarcane bagasse had performed by using aqueous ethylene glycol (30 v/v%) under 80 ℃ for 40 minutes, with solid to liquid of 1:20. It was found that the raw coconut husk comprised of 30.73 ± 1.7 % alphacellulose, 20.60 ± 4.1 % beta-cellulose, 12.62 ± 6.4 % gamma-cellulose and 36.89 ± 1.3 % lignin. Whereas, spent coffee ground composed of 22.68 ± 1.0 % alpha-cellulose, 19.56 ± 6.2 % beta-cellulose, 35.28 ± 7.5 % gamma-cellulose and 22.43 ± 0.2 % lignin. While raw sugarcane bagasse contained 41.01 ± 4.3 % alpha-cellulose, 9.506 ± 7.2 % beta-cellulose, 24.73 ± 2.7 % gamma-cellulose and 24.62 ± 0.3 % lignin. The highest delignification yield, hemicellulose removal rate, cellulose recovery and solid yield was observed for spent coffee ground with 14.60 ± 2.5 %, 22.29 ± 1.7 %, 26.50 ± 2.8 % and 87.07 ± 0.6 %, respectively. Furthermore, SEM-EDX, XRD and FTIR analysis had been carried out for the raw and treated biomass to study the impacts brought by pretreatment process in terms of structural morphology composition, crystallinity and functional groups. Various combination of biomass mixture had underwent the organosolv pretreatment to verify the result obtained. It was found the sample (E5) comprised of 50 wt.% SCG and 50 wt.% SB showed the best performance of organosolv pretreatment with the highest delignification yield of 15.98 ± 1.4 %, highest hemicellulose removal rate of 24.77 ± 3.9 % and highest total cellulose recovery of 24.34 ± 2.5 %. Several models had been developed to examine the possible factors that will impact the delignification yield and hemicellulose degradation rate. It was concluded that the higher the delignification yield and hemicellulose removal rate, the higher the cellulose recovery.